Evidence of Resistance to QoI Fungicides in Contemporary Populations of Mycosphaerella fijiensis, M. musicola and M. thailandica from Banana Plantations in Southeastern Brazil - Oliveira, Tamiris Y. K. [UNESP]; Silva, Tatiane C. [UNESP]; Moreira, Silvino I. [UNESP]; Christiano, Felix S. [UNESP]; Gasparoto, Maria C. G. [UNESP]; Fraaije, Bart A.; Ceresini, Paulo C. [UNESP] (MDPI, 2022)
Yellow and black Sigatoka, caused by Mycosphaerella fijiensis and M. musicola, respectively, are the most important worldwide foliar diseases of bananas. Disease control is heavily dependent on intensive fungicide sprays, which increase selection pressure for fungicide resistance in pathogen populations. The primary objective of this study was to assess the level and spread of resistance to quinone-outside inhibitors (QoI—strobilurin) fungicides in populations of both pathogens sampled from banana fields under different fungicide spray regimes in Southeastern Brazil. Secondly, we aimed to investigate when QoI resistance was confirmed if this was associated with the target-site alteration G143A caused by a mutation in the mitochondrial encoded cytochrome b gene. QoI resistance was detected in fungicide treated banana fields, while no resistance was detected in the organic banana field. A total of 18.5% of the isolates sampled from the pathogens’ populations were resistant to QoI. The newly described M. thailandica was also found. It was the second most abundant Mycosphaerella species associated with Sigatoka-like leaf spot symptoms in the Ribeira Valley and the highest level of QoI resistance was found for this pathogen. The G143A cytochrome b alteration was associated with the resistance to the QoI fungicides azoxystrobin and trifloxystrobin in M. fijiensis, M. musicola and M. thailandica strains. In order to reduce resistance development and maintain the efficacy of QoI fungicides, anti-resistance management strategies based on integrated disease management practices should be implemented to control the Sigatoka disease complex.
Keywords: black sigatoka; chemical control; cytochrome b; fungicide resistance; quinone-outside inhibitors (QoI); yellow sigatoka